The role of autonomy as a strategy for the financial performance of large acquisition targets : evidence from mergers and acquisitions on the London and Johannesburg stock exchanges - Barnard, Helena (University of Pretoria, 2025)
Thesis (PhD)--University of Pretoria, 2024.